A flexible bearing plate based on steel plate and rubber mat - Hou, Gui; Zheng, Guozhi; Zhang, Naitian (Frontiers in Materials, 2023)
The bearing plates used in the plate load test (PLT) in highway engineering are all rigid. The actual distribution of compressive stress at the bottom of the bearing plate cannot be acquired, so there is a particular deviation between the measured subgrade resilient modulus and the actual condition. A flexible bearing plate is used to test the subgrade to obtain a relatively accurate resilient modulus. In the ideal state, the compressive stress is equal everywhere. The distribution uniformity of the compressive stress should increase as much as possible. This paper uses variance and degree of mean deviation to evaluate the distribution uniformity of compressive stress quantitatively. The Combinatorial design of steel plate and rubber mat is considered to make the rigid-flexible bearing plate close to the flexible bearing plate. The thickness of the steel plate, the elastic modulus and thickness of the rubber mat, the friction coefficient(μ) between the bearing plate and the subgrade, and the combined shape characteristics of the rubber mat and the steel plate were studied in this paper. The relationship between the distribution uniformity of the compressive stress and the above influencing factors was obtained. Lubricant is used to reduce the friction between the rubber mat and subgrade as much as possible. A flexible bearing plate with relatively uniform compressive stress is designed. The computed results show that when μ=0.05, the variance is 0.0001, and the degree of mean deviation is 0.0780. The distribution uniformity of the compressive stress is very close to the uniform distribution load, which fully meets the accuracy requirements of engineering applications.